2019
DOI: 10.1093/geroni/igz038.2691
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Plant-Based Dietary Pattern on Dementia Risk: A Prospective Cohort Study.

Abstract: High antioxidants and phytochemicals from plant foods may protect against cognitive decline, while saturated fats from animal based foods considered as risk factors have been associated with dementia. Plant-based diets with limited animal products have been shown to improve glycemic control and reduce diabetes risk. The study aims to examine the association between vegetarian diet and dementia risk in a prospective cohort study. Quantitative data collected from 12,062 participants of Tzu Chi Vegetarian Study f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…As an example, kimchi (Korean traditional pickled cabbage) contains vitamin B12 and vitamin E, which were associated with better cognitive function (Chen et al, 2017), although the biological mechanisms need further investigation. In our analysis, the effect estimates on cognitive impairment of salt-preserved vegetables were shown to be beneficial, compared to Inverse associations between plant-based dietary patterns and cognitive function were reported in some (Lin et al, 2019;Okubo et al, 2017) but not in all studies, depending on the length of follow-up (Akbaraly et al, 2019;Medawar et al, 2019). For instance, a US cohort reported that neither the diet with high consumption of meats (OR = 1.06, 95% CI: 0.92, 1.22) nor the diet with high intake of fruits and vegetables at middle age (OR = 0.99, 95% CI: 0.88, 1.12) was associated with incident dementia in later life after a 20-year follow-up (Dearborn-Tomazos et al, 2019).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…As an example, kimchi (Korean traditional pickled cabbage) contains vitamin B12 and vitamin E, which were associated with better cognitive function (Chen et al, 2017), although the biological mechanisms need further investigation. In our analysis, the effect estimates on cognitive impairment of salt-preserved vegetables were shown to be beneficial, compared to Inverse associations between plant-based dietary patterns and cognitive function were reported in some (Lin et al, 2019;Okubo et al, 2017) but not in all studies, depending on the length of follow-up (Akbaraly et al, 2019;Medawar et al, 2019). For instance, a US cohort reported that neither the diet with high consumption of meats (OR = 1.06, 95% CI: 0.92, 1.22) nor the diet with high intake of fruits and vegetables at middle age (OR = 0.99, 95% CI: 0.88, 1.12) was associated with incident dementia in later life after a 20-year follow-up (Dearborn-Tomazos et al, 2019).…”
Section: Discussionmentioning
confidence: 55%
“…Inverse associations between plant‐based dietary patterns and cognitive function were reported in some (Lin et al., 2019 ; Okubo et al., 2017 ) but not in all studies, depending on the length of follow‐up (Akbaraly et al., 2019 ; Medawar et al., 2019 ). For instance, a US cohort reported that neither the diet with high consumption of meats (OR = 1.06, 95% CI: 0.92, 1.22) nor the diet with high intake of fruits and vegetables at middle age (OR = 0.99, 95% CI: 0.88, 1.12) was associated with incident dementia in later life after a 20‐year follow‐up (Dearborn‐Tomazos et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 Another cohort of 12,062 participants from Taiwan found that vegetarians had a 38% lower risk of dementia compared with non-vegetarians. 11 Nutritional solution or intervention for air pollution induced cardiopulmonary was introduced in several studies. These findings suggested plant-based food with higher antioxidants could reduce oxidative stress and inflammation in cardiovascular disease and other chronic inflammatory diseases induced by air pollution.…”
Section: Introductionmentioning
confidence: 99%
“…However, fermentation can improve nutritional properties by degrading phytates to improve mineral absorption [ 5 ]. For these reasons, scientists have focused on identifying novel food-grade strains with functional properties for plant-based fermentation [ 6 ].…”
Section: Introductionmentioning
confidence: 99%